Monitoring hemostasis parameters in left ventricular assist device recipients – a preliminary report - Hudzik, Bartosz; Kaczmarski, Jacek; Pacholewicz, Jerzy; Zakliczyński, Michał; Gąsior, Mariusz; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Mechanical circulatory support (MCS) therapy is associated with the improvement of long-term prognosis in patients with end-stage heart failure. For years it has been used as a bridge to transplant. However, more recently it is even being used as a destination therapy. Recently, clinicians have identified common MCS therapy-associated complications: pump thrombosis, bleeding, and hemolysis. These complications are very challenging with regard to both diagnosis and management. Aim : To determine time-dependant changes of selected hemostasis/coagulation parameters in patients with end-stage heart failure treated with MCS and antithrombotic therapy. Material and methods: Sixteen patients with end-stage heart failure on left ventricular assist device (LVAD) were followed for 6 weeks (six blood samples for each patient). Every week an extended hemostasis panel was assessed, including activated partial thromboplastin time, prothrombin time, international normalized ratio, von Willebrand factor (vWF) activity, factor VIII activity, fibrinogen level, D-dimer, platelet response to arachidonic acid (ASPI test) and adenosine diphosphate (ADP test), thrombin receptor activating peptide-6 (TRAP test) and collagen (COL test). Results : The study population comprised 16 men. The median time from LVAD implantation was 120 days (100–150 days). During the study period the D-dimer and fibrinogen concentrations were elevated but remained similar throughout all six measurements. Meanwhile factor VIII and vWF activities were elevated in the first two measurements and then subsequently declined. Inhibition of platelet aggregation was greater early after LVAD implantation. During subsequent weeks the inhibition of platelet aggregation was less pronounced. No patient developed any bleeding or thrombo-embolic event during the study period. Conclusions : Patients on MCS therapy demonstrate significant time-dependant changes in hemostasis parameters (both in the coagulation system and platelet aggregation).